2017
DOI: 10.4054/demres.2017.36.44
|View full text |Cite
|
Sign up to set email alerts
|

Spatial modelling of rural infant mortality and occupation in 19th-century Britain

Abstract: BACKGROUND Infant mortality in 19th century rural places has been largely neglected: to study it offers new insight into rural demography.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 30 publications
1
5
0
Order By: Relevance
“…Despite this, population density was still independently significant, probably capturing the fact that sanitation and water supply struggled to keep up with population growth in Victorian and Edwardian cities. In line with previous research, the analysis of local occupational and social class structure confirmed that mining and textile districts experienced poor childhood survival, and the districts determined by large share of agricultural workers had relatively low mortality in early childhood (Gregory 2008;Atkinson et al 2017aAtkinson et al , 2017b.…”
Section: Discussionsupporting
confidence: 57%
See 2 more Smart Citations
“…Despite this, population density was still independently significant, probably capturing the fact that sanitation and water supply struggled to keep up with population growth in Victorian and Edwardian cities. In line with previous research, the analysis of local occupational and social class structure confirmed that mining and textile districts experienced poor childhood survival, and the districts determined by large share of agricultural workers had relatively low mortality in early childhood (Gregory 2008;Atkinson et al 2017aAtkinson et al , 2017b.…”
Section: Discussionsupporting
confidence: 57%
“…This could be related to different causes but might be reflecting our study's general limitations in the ability to measure all district-level differences in the development of public health and sanitation, local infectious disease environment, access to basic healthcare, or women's work and childcare. For example, the labour intensity of women's agricultural work in eastern England has been identified as a possible reason for high levels of infant mortality in that region (Sneddon 2006;Hinde and Fairhurst 2015;Atkinson 2017b). Women's agricultural work may have curtailed breastfeeding and so increased infant mortality but had a less detrimental effect on older children.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, in terms of future work and taking inspiration on recent studies within the realm of the spatial humanities, we also plan to experiment with the inclusion of other types of ancillary variables (e.g., proximity towards the historical transportation network [19][20][21], or information on building footprints obtained from the segmentation of historical maps [64]), and with other types of spatial disaggregation tasks that involve historical datasets (e.g., disaggregation of indicators relative to health problems [65][66][67][68][69] or historical tourism [70,71]), leveraging ancillary data collected from textual sources through the application of geographical text analysis. Although the present study focused on the disaggregation of population counts, the proposed methods can naturally also be applied in the disaggregation of socio-economic indicators relevant for different types of historical inquiries.…”
Section: Discussionmentioning
confidence: 99%
“…In the digital humanities, a variety of textual sources including travel writings ( Donaldson et al, 2017 ), census records ( Atkinson et al, 2017 ), newspapers and periodicals ( Porter et al, 2018 ) have been interrogated using different techniques. Geographical Text Analysis (GTA) ( Donaldson et al, 2017 , Gregory and Donaldson, 2016 ) is one such research area having particular relevance in the extraction of historical flora from texts.…”
Section: Related Workmentioning
confidence: 99%